Microbiological quality of raw goat's milk - Lim, Evonne Pei Qin; Hassan, Latiffah; Abdul Aziz, Saleha; Bejo, Siti Khairani (2011)
A study was conducted to determine the microbiological status of raw goat’s milk from a few sources in Selangor and to detect milk-borne pathogens; especially Staphylococcus aureus, Salmonella spp., Campylobacter spp., and Brucella melitensis. Forty samples from nine different sources in Selangor were collected. The study found that the samples had a mean Total Plate Count (TPC) of 5.2 ± 1.36 x 106 cfu/mL. Staphylococcus aureus were detected in 14 of 40 sampels of raw goat’s milk (35%). Salmonella spp. Campylobacter spp. and Brucella melitensis were not isolated from any of the samples.